Tipe Kepemimpinan Ny. Hj. Dra. Mahmudah Hisyam Dalam Memimpin Asrama Roudlotul Qur’an Pesantren Darussalam Putri Blokagung - Siti Aimah; Lely Ana Ferawati Ekaningsih (IAI Darussalam, 2017)
The purpose of this study are: (1) To know Nyai leadership type. Hj. Dra. Mahmudah Hisyam in leading the roudlotul Qur’an boarding school of Darussalam daughters of Blokagung; (2) To know the efforts made Nyai. Hj. Mahmudah Hisyam in improving the success of the recitation santri tahfidzul Qur’an; (3) To know Nyai's leadership technique. Hj. Dra. Mahmudah Hisyam in leading santri tahfidzul Qur’an.Dengan using qualitative research methods and three techniques of data collection that is observation partisispan, in-depth interviews and documentation obtained the results of research indicating that: (1) In leading dormitory Roudlotul Qur`an Pondok Pesantren Darussalam Ny. Hj. Dra. Mahmudah Hisyam uses the Laissez Faire type but is still under observation of kyai, democratic and charismatic but the most dominant among the three types is the type of charismatic. (2) Efforts made by Ny. Hj. Dra. Mahmudah Hisyam in leading boarding Roudlotul Qur'an Pondok Pesantren Darussalam North Princess is: (a) Good example; (b) Religious leaders; (c) Protector; (d) Communicators; (e) Advisers; (f) Person in charge; (g) Teachers and educators. (3) Technique performed by Ny. Hj. Dra. Mahmudah Hisyam in leading santri tahfidzul Qur`an is to provide supervision or supervision that coordinate directly with related stakeholders, namely the chairman of boarding Roudlotul Qur`an, head of Darussalam Putri pesantren, wali santri and boarding board of tahfidzul Qur'an as Banyuwangi district which is incorporated in the Jam'iyah Hifdzul Qur'an (JHQ) organization.